Dust effect on PV modules - Hassan Qasem; Tom Betts; Harald Mullejans; H. AlBusairi; Ralph Gottschalg (2011)
This paper investigates the effect of dust on photovoltaic (PV) modules with respect to dust concentration, wavelength and spectral transmittance. Dust samples were collected from Kuwait in the form of raw dust and accumulated dust on sample glass at different tilt angles. The spectral transmittance was measured in the Centre for Renewable Energy Systems Technology (CREST) laboratory with a spectrophotometer. Spectral transmittance variation was identified for samples at different tilted positions, where the worst case was presented at a tilt angle of 30o with a non uniformity of 4.4% in comparison to 0.2% for the 90o tilt between the top, middle and bottom. The effect of this on PV is investigated by calculating a modified spectral response for different technologies using spectral response data measured by the European Solar Test Installation (ESTI). The measured data showed a faster rate of decrease in transmittance at wavelengths